Implementing Qishash from the Maqashid Syariah Perspective: Analysis of Life Protection in Jinayah Law - Ahmad Ansori (Rechtsvinding, 2026)
This research departs from the problematic dichotomous understanding of Qishash which is often reduced to a cruel law of revenge, or conversely, its formal application is encouraged without a complete understanding of its philosophy. This study aims to analyze the urgency of implementing Qishash through the lens of Maqashid Syariah with a focus on its effectiveness as an instrument of life protection (ḥifẓ al-nafs) in jinayah law. Using a qualitative library research method, this study conducted an in-depth review of primary and secondary sources related to Qishash, Maqashid Syariah, and comparative criminal law. The results of the study show that: First, Qishash within the Maqashid framework is not the final goal, but rather a definitive means to achieve ḥifẓ al-nafs as primary dharūriyyāt through the enforcement of equal justice and balance; Second, Its effectiveness as a zawājir (deterrent) and wiqāyah (protection) lies in the logic of certainty, proportionality, and restoration of victims' rights; Third, Its contextualization in the modern system can be done through the integration of its substantive values into the restorative justice framework and strengthening the role of victims; Fourth, Comparative analysis reveals the superiority of Qishash in victim justice and theoretical deterrence, even though the conventional system excels in procedural guarantees. In conclusion, the urgency of Qishash lies in its spirit and philosophy which offers a victim-centered justice perspective and substantive soul protection. Its implementation can be realized through the socialization of the Maqashid concept, the integration of the values of proportionality and restitution into national criminal law policies, and the strengthening of restorative approaches that take into account the interests of victims.